Problematika Pembuktian dan Pertanggungjawaban Pelaku dalam Kekerasan Seksual Non-Fisik: Analisis Hukum Acara Pidana Indonesia - Novi Enjelina Putri; Elma Amalia (Journal of Law and Administrative Science, 2026)
Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) introduces legal breakthroughs by criminalizing non-physical sexual violence that was previously difficult to address through existing criminal law instruments. However, the implementation of evidentiary procedures for these offenses faces various systemic challenges within the framework of Indonesian Criminal Procedure Law (KUHAP). This study aims to analyze the evidentiary problems of non-physical sexual violence, perpetrator criminal accountability, and structural weaknesses of KUHAP in handling such cases. The research method employed is juridical-normative with statutory, conceptual, and comparative law approaches. The results reveal five main problems: (1) difficulties in proving immaterial acts; (2) insufficiency of conventional evidence; (3) proving perpetrator's mens rea; (4) re-victimization of victims in court proceedings; and (5) inconsistency of judicial interpretation. Criminal accountability of perpetrators is hampered by the absence of specific constructions in KUHAP for psychological and digital-based violence. This study recommends KUHAP reform through expanded recognition of electronic evidence, burden of proof reforms, and strengthened victim protection mechanisms.